2007
DOI: 10.1016/j.brainres.2006.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention facilitates selection of illusory objects: Evidence from event-related brain potentials

Abstract: The relationship between spatial attention and object-based attention has long been debated. On the basis of behavioral evidence it has been hypothesized that these two forms of attention share a common mechanism, such that directing spatial attention to one part of an object facilitates the selection of the entire object. In a previous study (Martinez et al., 2006) we used recordings of eventrelated potentials (ERPs) during a paradigm modeled after that of Egly et al. (1994) to investigate this relationship. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 47 publications
(75 reference statements)
9
34
3
Order By: Relevance
“…Since P1 is known to indicate the distribution of spatial attention (e.g., Hillyard et al, 1996;Luck, Heinze, Mangun, & Hillyard, 1990), this result, together with the results from other ERP studies (e.g., Martínez et al, 2007;Martínez et al, 2006) and fMRI and single-cell recording studies (e.g., Müller & Kleinschmidt, 2003;Roelfsema et al, 1998), provides physiological evidence supporting the location-mediated selection of object-based attention. Matsukura and Vecera (2011) recently proposed that a spatially invariant representation could occur under conditions when objects were clearly segregated.…”
Section: Mechanisms That Give Rise To Object Effectssupporting
confidence: 69%
See 2 more Smart Citations
“…Since P1 is known to indicate the distribution of spatial attention (e.g., Hillyard et al, 1996;Luck, Heinze, Mangun, & Hillyard, 1990), this result, together with the results from other ERP studies (e.g., Martínez et al, 2007;Martínez et al, 2006) and fMRI and single-cell recording studies (e.g., Müller & Kleinschmidt, 2003;Roelfsema et al, 1998), provides physiological evidence supporting the location-mediated selection of object-based attention. Matsukura and Vecera (2011) recently proposed that a spatially invariant representation could occur under conditions when objects were clearly segregated.…”
Section: Mechanisms That Give Rise To Object Effectssupporting
confidence: 69%
“…Results in support of the sensory enhancement account can also be found in a number of other ERP experiments, including X. He et al (2004He et al ( , 2008, Martínez et al (2007;Martínez et al, 2006), and Weber et al (1997). Despite the differences in their methodology (e.g., using exogenous or endogenous cues or a postdisplay probe to measure the distribution of spatial attention), a common finding is that object-based attention is associated with an enhanced N1 component over the occipito-temporal areas (but see Weber et al, 1997, for a larger N1 amplitude in the different-object condition than in the same-object condition).…”
Section: Mechanisms That Give Rise To Object Effectssupporting
confidence: 68%
See 1 more Smart Citation
“…Many ERP studies have noted an enhancement of N1 in response to stimuli that belong to an unattended region of an attended object, both for spatial cueing and sustained-attention tasks using physical or illusory rectangles (He et al, 2004;Kasai, 2010;Martínez et al, 2006Martínez et al, , 2007aMartínez et al, , 2007b, or human-head geometry or connectedness (Verliger et al, 2008). This convergent evidence for an object-based N1 attention effect may indicate a single and general selection process for object-based attention, which is partly shared with spatial attention.…”
Section: Introductionmentioning
confidence: 94%
“…According to this view, spatial attention directed to one part of an object spreads throughout its boundaries and strengthens the sensory representation of the entire object. In support of this "objectguided spatial-selection mechanism," physiological studies using variants of the dual-rectangle paradigm of Egly et al (1994) have shown that neural activity patterns associated with spatial and object-based attention have much in common, as evidenced by functional magnetic resonance imaging (fMRI) (Müller and Kleinschmidt, 2003) and event-related potential (ERP) recordings (He et al, 2004;Martinez et al, 2006Martinez et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%